Rheological performance of high alumina nano-bonded refractory castables containing carboxylic acids as additives. Issue 9 (November 2015) - Nouri-Khezrabad, M.; Salvini, V.R.; Luz, A.P.; Golestani-Fard, F.; Rezaie, H.R.; Pandolfelli, V.C.
Abstract: This paper evaluated the role played by citric acid and gallic acid in high alumina colloidal silica-bonded castables. The addition of citric acid to three different types of colloidal silica-containing compositions led to distinct flow behavior. Vibrating flow measurements were carried out in order to define the castables׳ workability. Zeta potential and specific conductivity tests were also used to analyze the effect of the selected carboxylic acids in alumina-colloidal silica suspensions. Furthermore, other important parameters considered during the evaluation of such additives were: a) pH of the colloidal silica binder and b) pK a values of the carboxylic acid. The higher the pH of the nano-binder solution, the less adsorption of carboxylic acid on the alumina surface will take place. As a result, molecules presenting acidic pK a values such as citric acid are effective additives for colloidal silica binders with pH≤10, whereas others with alkaline pK a values (e.g. gallic acid) can be used with colloidal silica sources presenting higher pH. The use of the mentioned carboxylic acids is required to provide enough workability to the system due to a retarding effect on the setting agent.